Method for preparing large-size low-segregation cu-15sn alloy by electromagnetic confinement
Patent Information
- Application Number
- CN202611172498.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-09-25
AI Technical Summary
[0004]本发明的目的是提供一种通过电磁约束制备大尺寸低偏析Cu-15Sn合金的方法,解决现有工艺制备大尺寸合金时Sn溶质偏析严重、晶粒粗大、Sn固溶度低、塑韧性差、组织不均的缺陷,借助交变电磁场协同水冷激冷与定向热流调控,细化晶粒、均匀溶质分布,提升Sn固溶度,制得组织均匀、性能优良的40kg级大尺寸Cu-15Sn铸锭
针对大尺寸Cu-15Sn合金现有制备技术中溶质偏析严重、晶粒粗大、过冷度区间窄、Sn元素固溶度低及包晶转变难以抑制等瓶颈问题,本发明提供了一种结合无底座坩埚底部水冷激冷、交变电磁场协同驱动、定向抽拉热流调控的组合方法,与现有技术相比,本发明方法将熔炼坩埚、导流管、无底座坩埚和水冷铜结晶器连续同轴布置,并结合翻转浇注工艺,使40kg级金属熔体在同一真空环境内连续完成熔炼、浇注和定向凝固,有效减少了熔体转运过程中的温降及二次污染,提高了大尺寸Cu-15Sn合金连续制备的稳定性和工艺可靠性。
Smart Images

Figure CN122811569A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of alloy preparation methods, and relates to a method for preparing large-size, low-segregation Cu-15Sn alloys by electromagnetic confinement. Background Technology
[0002] Cu-Sn alloys are an important raw material in the field of high field strength Nb3Sn superconducting wires. Their effective mechanical properties and solid solubility play a crucial role in the preparation and service of Nb3Sn superconducting wires. However, Cu-Sn alloys exhibit compositional segregation during solidification, which leads to a decrease in the alloy's ductility and toughness. In addition, compositional segregation can also cause the enrichment of solutes inside the alloy, resulting in uneven overall mechanical properties.
[0003] Cu-Sn alloys not only require excellent mechanical properties, but the improved microstructure uniformity resulting from high solid solubility is also a reliable guarantee for the production and service of superconducting wires. Currently, the main methods for preparing Cu-Sn alloys are induction melting casting and the Japanese Mizuta process. Induction melting casting has a slow solidification rate and prolonged cooling time, making it prone to phase transformation at the solid-liquid interface. This promotes the continuous growth of second-phase grains within the Cu-Sn alloy, leading to grain coarsening, significantly reducing the overall alloy performance, and exacerbating material brittleness. Furthermore, the casting size is limited, failing to meet the process requirements for large-size Cu-Sn alloys. The Japanese Mizuta process can meet the process requirements for large-size Cu-Sn alloys, but its effect on improving microstructure segregation in large-size Cu-Sn alloys is limited, failing to significantly eliminate compositional segregation. In addition, when the Sn content reaches 15 wt.%, segregation and brittle phases easily appear, confining the room-temperature tensile elongation of Cu-Sn alloys to 8%–12%. Moreover, the temperature gradient decays towards the end of solidification, easily leading to the formation of impurities and disrupting the continuity of the directional microstructure. Furthermore, uneven solute redistribution leads to significant compositional differences between dendrite trunks and interdendrites, resulting in element enrichment and depletion zones. This affects the uniformity of the microstructure, causing a decrease in the ductility and toughness of large-size Cu-Sn alloys, reducing fatigue and endurance performance, and consequently affecting the service life of copper-tin alloy materials, making it difficult to meet the requirements of high-end applications. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing large-size, low-segregation Cu-15Sn alloys by electromagnetic confinement, which solves the defects of existing processes in preparing large-size alloys, such as severe Sn solute segregation, coarse grains, low Sn solid solubility, poor plasticity and toughness, and uneven microstructure. By using alternating electromagnetic fields in conjunction with water cooling and directional heat flow control, the grains are refined, the solute distribution is uniform, and the Sn solid solubility is improved, resulting in 40kg-class large-size Cu-15Sn ingots with uniform microstructure and excellent performance.
[0005] The technical solution adopted in this invention is a method for preparing large-size, low-segregation Cu-15Sn alloys by electromagnetic confinement, specifically as follows: Step 1: Weigh oxygen-free copper and high-purity tin according to the composition of Cu-15Sn alloy, then process the copper block with blind holes and encapsulate the tin granules; assemble the melting crucible, guide tube, baseless crucible and water-cooled copper crystallizer coaxially from top to bottom in the vacuum induction furnace, and set cooling water channels inside the crystallizer and the induction furnace pull rod. Step 2: Place the raw materials into the melting crucible and seal the pouring channel; turn on the crystallizer and pull rod to cool the circulation. Step 3: Melt the Cu-15Sn alloy; Step 4: Pour the molten alloy into a baseless crucible, keep it warm, and then begin the pulling process. Apply alternating current during the pulling process. After the pulling is completed, a Cu-15Sn alloy ingot is obtained.
[0006] The invention is further characterized by: In step 1, the total mass of the alloy is ≤50kg, and the purity of both copper and tin is 99.99%. After the metal raw materials are weighed, they are ultrasonically cleaned and dried. The top of the copper block is cut to obtain a copper plate. Blind holes are machined on the cut surface, tin granules are inserted into the blind holes, and a copper plate is placed on top of the blind holes for encapsulation.
[0007] In step 1, the smelting crucible is made of high-purity graphite.
[0008] In step 1, the bottom of the baseless crucible is in contact with the water-cooled copper crystallizer, and the two are fitted with an interference fit.
[0009] In step 2, the specific steps for sealing the pouring channel are as follows: take graphite paper with a carbon content >99.5% and lay it along the inner wall of the funnel to ensure that the graphite paper is completely attached to the inner wall of the funnel; after sealing the pouring channel, turn on the high-speed cooling circulating water inside the water-cooled copper crystallizer and the pull rod.
[0010] Step 3 specifically involves: The mechanical pump, Roots pump, fore-stage valve, and diffusion pump are turned on in sequence to evacuate the directional solidification furnace to the set vacuum level. The heating program is started to heat the holding zone, so that the baseless crucible can establish a stable axial temperature gradient. After the temperature of the holding zone rises to 800℃~1100℃, the induction power supply is turned on to heat the melting crucible and start melting Cu-15Sn alloy. During the melting process, the water-cooled copper crystallizer and the high-speed circulating cooling water inside the pull rod are kept running continuously.
[0011] In step 3, the specific smelting process is as follows: Start melting at 6kW, increasing by 1kW to 4kW every 10 to 40 minutes. Once the Cu-15Sn alloy in the melting crucible is completely melted and a stable vortex forms on the surface of the molten metal, adjust to 8kW for refining for 2 to 10 minutes.
[0012] Step 4 specifically involves: Molten Cu-15Sn alloy liquid was poured into a baseless crucible using a flip-casting method and held in the holding zone for 10 to 40 minutes. A 20Hz alternating electromagnetic field was applied by a low-frequency AC device, with the electromagnetic field concentrated on the liquid-solid interface region of the baseless crucible. A pulling device was started at a pulling rate of 100 to 250 μm / s, keeping the baseless crucible fixed. The pulling rod moved the solidified ingot downwards, and the bottom of the ingot continuously contacted the water-cooled copper crystallizer to dissipate latent heat and maintain the stability of the liquid-solid interface. After continuous pulling for 3000 seconds, the pulling device and electromagnetic field were turned off, and the furnace was cooled to room temperature to obtain the Cu-15Sn alloy ingot.
[0013] The beneficial effects of this invention are: To address the bottlenecks in existing large-size Cu-15Sn alloy preparation technologies, such as severe solute segregation, coarse grains, narrow undercooling range, low Sn solid solubility, and difficulty in suppressing peritectic transformation, this invention provides a combined method integrating bottom water-cooling quenching of a baseless crucible, synergistic driving with alternating electromagnetic fields, and directional pulling heat flow control. Compared with existing technologies, this invention arranges the melting crucible, guide tube, baseless crucible, and water-cooled copper crystallizer coaxially in a continuous manner, and combines it with a flipping casting process, enabling 40kg-class molten metal to continuously complete melting, casting, and directional solidification in the same vacuum environment. This effectively reduces temperature drop and secondary contamination during melt transfer, and improves the stability and process reliability of continuous preparation of large-size Cu-15Sn alloys.
[0014] Furthermore, the core innovation of this invention lies in the synergistic coupling of three technologies rather than a simple superposition, achieving comprehensive intervention in the solidification process from multiple dimensions, including nucleation, growth, heat transfer, and mass transfer: First, the bottom of the baseless crucible directly contacts the high-speed water-cooled copper crystallizer, causing significant undercooling of the Cu-15Sn liquid alloy at the moment of pouring, resulting in a dense and fine initial grain structure, providing an excellent seed substrate for subsequent directional growth; based on this, while initiating pull-out to achieve directional solidification, an alternating magnetic field is applied, and the alternating electromagnetic field mainly acts on the region near the liquid-solid interface within the baseless crucible, promoting moderate convection of the melt at the liquid-solid interface front while suppressing the overall flow of the large-size molten pool, preventing molten metal overflow; on the one hand, a dual effect of temperature gradient driving and electromagnetic force driving is formed, which, through forced convection disturbance of the solute field at the solid-liquid interface front, microscopically... Breaking the limitations of solute diffusion restricted by traditional single temperature gradient driving, this method significantly suppresses interdendritic segregation in Cu-Sn alloys. On the other hand, the alternating electromagnetic field effectively broadens the actual solidification undercooling range of Cu-15Sn alloys, overcoming the kinetic limitation of small undercooling in conventional directional solidification, and providing a wider process window for fine microstructure control. More importantly, the heat flow control and electromagnetic confinement during directional solidification produce a synergistic effect, accelerating melt heat dissipation and promoting rapid cooling while providing more solid solution channels for Sn solute atoms. This effectively alleviates the solid solution resistance caused by the size mismatch between Sn atoms and Cu matrix atoms, thereby significantly improving the limiting solid solubility of Sn in the Cu matrix and achieving uniform solid solution of the solute. At the same time, by suppressing the peritectic transformation at the solid-liquid interface, an ingot with a single solid solution structure is obtained.
[0015] Under the synergistic effect of the above-mentioned multiple mechanisms, the method of the present invention finally produces Cu-15Sn alloy ingots with fine-grained matrix, axially oriented grains and uniform equiaxed grain distribution, small and dispersed Sn-rich phase, and uniform Sn element solid solution. It effectively solves the inherent defects of Cu-15Sn alloys prepared by traditional directional solidification, such as prominent anisotropy and poor microstructure, and achieves comprehensive optimization of overall performance. Compared with traditional preparation technology, it shows significant and irreplaceable technical advantages. Attached Figure Description
[0016] Figure 1 These are comparative microstructure images of the Cu-15Sn alloys prepared in Example 3 and Comparative Example 1; Figure 2 These are the mechanical property comparison curves of the Cu-15Sn alloys prepared in Example 3 and Comparative Example 1; Figure 3 These are the conductivity comparison curves of the Cu-15Sn alloys prepared in Example 3 and Comparative Example 1; Figure 4These are XRD comparison patterns of the Cu-15Sn alloys prepared in Example 3 and Comparative Example 1. Detailed Implementation
[0017] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.
[0018] This invention relates to a method for preparing large-size, low-segregation Cu-15Sn alloys using electromagnetic confinement, which is implemented according to the following steps: Step 1: Weigh oxygen-free copper and high-purity tin materials with a total mass ≤50kg and a purity of 99.99% using a high-precision electronic scale according to the Cu-15Sn alloy composition. Place the prepared metal materials into an ultrasonic cleaner for ultrasonic cleaning, and then blow them dry for later use.
[0019] Cut the top of the copper block to obtain a copper plate. Machine a blind hole on the cut surface, fill the blind hole with high-purity tin granules, and cover the top of the blind hole with a copper plate for encapsulation.
[0020] The melting crucible of the vacuum induction furnace is adjusted to the charging position. A baseless crucible is installed below the melting crucible. The bottom of the baseless crucible is assembled with the water-cooled copper crystallizer using a gradient contact sealed crystallization structure. The two are interference-fitted, allowing the molten metal to directly contact the water-cooled copper platform. The melt moves with the pull-out device, achieving layer-by-layer solidification along the temperature gradient. The two are tightly fitted, forming a continuous guiding channel between the outlet of the baseless crucible and the inlet of the water-cooled copper crystallizer. A circulating cooling water channel is installed inside the water-cooled copper crystallizer, and a cooling water channel is simultaneously installed inside the pull-out rod. Both are circulated with high-speed cooling water, forming a continuous device structure with melting at the top and directional solidification at the bottom.
[0021] Step 2: The copper-based tin-embedded particle preform from Step 1, after ultrasonic cleaning and drying, is transferred into the melting crucible of the vacuum induction furnace. The melting crucible is made of high-purity graphite. Then, the casting channel is sealed: graphite paper with a carbon content >99.5% is laid along the inner wall of the funnel, ensuring complete adhesion between the graphite paper and the inner wall to improve the sealing performance of the casting system; a guide pipe is installed to keep the melting crucible, guide pipe, and baseless crucible coaxial, ensuring the inner wall of the baseless crucible is smooth and free of scratches. Then, the water-cooled copper crystallizer and the internal circulating cooling system of the pull rod are activated, allowing high-speed cooling water to circulate continuously.
[0022] Step 3: Sequentially turn on the mechanical pump, Roots pump, fore-stage valve, and diffusion pump to evacuate the directional solidification furnace to the set vacuum level. Start the heating program to heat the holding zone, establishing a stable axial temperature gradient in the baseless crucible. Once the holding zone temperature reaches 800–1100°C, start the induction power supply to heat the melting crucible and begin melting the Cu-15Sn alloy. Start melting at 6kW, increasing the kW by 1–4kW every 10–40 minutes. When the Cu-15Sn alloy in the melting crucible is completely melted and a stable vortex forms on the surface of the molten metal, adjust the kW to 8kW for refining for 2–10 minutes. During the refining process, maintain continuous high-speed circulating cooling water in the water-cooled copper crystallizer and inside the pull rod to ensure the crystallizer maintains stable cooling capacity and forms a stable liquid-solid interface at the junction of the bottom of the baseless crucible and the water-cooled copper crystallizer.
[0023] Step 4: Molten Cu-15Sn alloy is poured into a baseless crucible using a flip-casting method. The molten metal flows continuously into the baseless crucible in the lower holding zone through a guide pipe and is held for 10–40 minutes. Then, a low-frequency AC current output device is activated, applying an AC current of 20Hz. This ensures the AC electromagnetic field primarily acts on the region near the liquid-solid interface of the baseless crucible, promoting melt flow and uniform solute distribution. Next, a pulling program is set, with the pulling rate set to 100–250 μm / s, and the pulling device is activated. During the pulling process, the baseless graphite crucible remains stationary, with only the pulling rod slowly and continuously moving the solidified Cu-15Sn alloy ingot downwards. The bottom of the solidified alloy ingot remains in direct contact with the water-cooled copper crystallizer, rapidly forming a stable solidified shell under the action of high-speed circulating cooling water, continuously dissipating latent heat of solidification, thus maintaining a stable liquid-solid interface at the junction of the baseless crucible bottom and the water-cooled copper crystallizer. As the pulling process continues, molten metal is continuously replenished to the liquid-solid interface to complete continuous solidification. After pulling for 3000 seconds, the pulling and electromagnetic field output are stopped, and the mixture is cooled to room temperature to obtain a 40kg Cu-15Sn alloy ingot.
[0024] Example 1 Step 1: Weigh 40 kg of oxygen-free copper and high-purity tin (6 kg tin, 34 kg copper) with a purity of 99.99% using a high-precision electronic scale according to the Cu-15Sn alloy composition. Place the prepared metal raw materials into an ultrasonic cleaner for ultrasonic cleaning, and then dry them for later use. Machine blind holes on the end face of the copper block, and load high-purity tin granules into it according to the element ratio. Cover the top of the blind holes with a copper plate for sealing. Adjust the upper melting crucible to the loading position, and install the baseless crucible (120 mm inner diameter, 300 mm height) below. The bottom of the baseless crucible and the water-cooled copper crystallizer are assembled using a gradient contact sealed crystallization structure, with the two fitting tightly together to form a continuous guiding channel between the outlet of the baseless crucible and the inlet of the water-cooled copper crystallizer. The water-cooled copper crystallizer is equipped with a circulating cooling water channel, and the pull rod is also equipped with a cooling water channel. Both are circulated with high-speed cooling water, forming a continuous device structure of upper melting and lower directional solidification.
[0025] Step 2: The copper-based tin-embedded particle preform from Step 1, after ultrasonic cleaning and drying, is transferred into the melting crucible of the vacuum induction furnace. The melting crucible is made of high-purity graphite. Then, the casting channel is sealed: graphite paper with a carbon content >99.5% is laid along the inner wall of the funnel, ensuring complete adhesion between the graphite paper and the funnel wall to improve the sealing performance of the casting system; a guide pipe is installed to ensure the melting crucible, guide pipe, and baseless crucible are coaxial, and the inner wall of the baseless crucible is checked for smoothness and scratches. Then, the water-cooled copper crystallizer and the internal circulating cooling system of the pull rod are started, allowing high-speed cooling water to circulate continuously.
[0026] Step 3: Sequentially turn on the mechanical pump, Roots pump, fore-stage valve, and diffusion pump to evacuate the directional solidification furnace to the set vacuum level. Start the heating program to heat the holding zone, establishing a stable axial temperature gradient in the baseless crucible. Once the holding zone temperature reaches 800°C, start the induction power supply to heat the melting crucible and begin melting the Cu-15Sn alloy. Start melting at 6kW, increasing by 1kW every 10 minutes. When the Cu-15Sn alloy in the melting crucible is completely melted and a stable vortex forms on the surface of the molten metal, adjust to 8kW for refining for 2 minutes. During the refining process, maintain continuous high-speed circulating cooling water inside the water-cooled copper crystallizer and the pull rod to ensure the crystallizer maintains stable cooling capacity and forms a stable liquid-solid interface at the junction of the bottom of the baseless crucible and the water-cooled copper crystallizer.
[0027] Step 4: Molten Cu-15Sn alloy is poured into a baseless crucible using a flip-casting method. The molten metal flows continuously into the baseless crucible in the lower heat-preserving zone through a guide pipe and is held for 10 minutes. Then, a low-frequency AC current output device is activated, applying an AC current of 20Hz. This ensures the AC electromagnetic field primarily acts on the region near the liquid-solid interface of the baseless crucible, promoting melt flow and uniform solute distribution. Next, a pulling program is set, with the pulling rate set to 100μm / s, and the pulling device is activated. During the pulling process, the baseless graphite crucible remains stationary, with only the pulling rod slowly and continuously moving the solidified Cu-15Sn alloy ingot downwards. The bottom of the solidified alloy ingot remains in direct contact with the water-cooled copper crystallizer, rapidly forming a stable solidified shell under the action of high-speed circulating cooling water, continuously dissipating latent heat of solidification, thus maintaining a stable liquid-solid interface at the junction of the baseless crucible bottom and the water-cooled copper crystallizer. As the pulling process continues, molten metal is continuously replenished to the liquid-solid interface to complete continuous solidification. After pulling for 3000 seconds, the pulling and electromagnetic field output are stopped, and the mixture is cooled to room temperature to obtain a 40kg Cu-15Sn alloy ingot.
[0028] Example 2 Step 1: Weigh 40 kg of oxygen-free copper and high-purity tin (6 kg tin, 34 kg copper) with a purity of 99.99% using a high-precision electronic scale according to the Cu-15Sn alloy composition. Place the prepared metal raw materials into an ultrasonic cleaner for ultrasonic cleaning, and then dry them for later use. Machine blind holes on the end face of the copper block, and load high-purity tin granules into it according to the element ratio. Cover the top of the blind holes with a copper plate for sealing. Adjust the upper melting crucible to the loading position, and install the baseless crucible (120 mm inner diameter, 300 mm height) below. The bottom of the baseless crucible and the water-cooled copper crystallizer are assembled using a gradient contact sealed crystallization structure, with the two fitting tightly together to form a continuous guiding channel between the outlet of the baseless crucible and the inlet of the water-cooled copper crystallizer. The water-cooled copper crystallizer is equipped with a circulating cooling water channel, and the pull rod is also equipped with a cooling water channel. Both are circulated with high-speed cooling water, forming a continuous device structure of upper melting and lower directional solidification.
[0029] Step 2: The copper-based tin-embedded particle preform from Step 1, after ultrasonic cleaning and drying, is transferred into the melting crucible of the vacuum induction furnace. The melting crucible is made of high-purity graphite. Then, the casting channel is sealed: graphite paper with a carbon content >99.5% is laid along the inner wall of the funnel, ensuring complete adhesion between the graphite paper and the funnel wall to improve the sealing performance of the casting system; a guide pipe is installed to ensure the melting crucible, guide pipe, and baseless crucible are coaxial, and the inner wall of the baseless crucible is checked for smoothness and scratches. Then, the water-cooled copper crystallizer and the internal circulating cooling system of the pull rod are started, allowing high-speed cooling water to circulate continuously.
[0030] Step 3: Sequentially turn on the mechanical pump, Roots pump, fore-stage valve, and diffusion pump to evacuate the directional solidification furnace to the set vacuum level. Start the heating program to heat the holding zone, establishing a stable axial temperature gradient in the baseless crucible. Once the holding zone temperature reaches 900℃, start the induction power supply to heat the melting crucible and begin melting the Cu-15Sn alloy. Start melting at 6kW, increasing by 2kW every 20 minutes. When the Cu-15Sn alloy in the melting crucible is completely melted and a stable vortex forms on the surface of the molten metal, adjust to 8kW for refining for 4 minutes. During the refining process, maintain continuous high-speed circulating cooling water inside the water-cooled copper crystallizer and pull rod to ensure the crystallizer maintains stable cooling capacity and forms a stable liquid-solid interface at the junction of the bottom of the baseless crucible and the water-cooled copper crystallizer.
[0031] Step 4: Molten Cu-15Sn alloy is poured into a baseless crucible using a flip-casting method. The molten metal flows continuously into the baseless crucible in the lower heat-preserving zone through a guide pipe and is held for 20 minutes. Then, a low-frequency AC current output device is activated, applying a 20Hz AC current to ensure the AC electromagnetic field primarily acts on the area near the liquid-solid interface of the baseless crucible, promoting melt flow and uniform solute distribution. Next, a pulling program is set, with the pulling rate set to 150μm / s, and the pulling device is activated. During the pulling process, the baseless graphite crucible remains stationary, with only the pulling rod slowly and continuously moving the solidified Cu-15Sn alloy ingot downwards. The bottom of the solidified alloy ingot remains in direct contact with the water-cooled copper crystallizer, rapidly forming a stable solidified shell under the action of high-speed circulating cooling water, continuously dissipating latent heat of solidification, thus maintaining a stable liquid-solid interface at the junction of the baseless crucible bottom and the water-cooled copper crystallizer. As the pulling process continues, molten metal is continuously replenished to the liquid-solid interface to complete continuous solidification. After pulling for 3000 seconds, the pulling and electromagnetic field output are stopped, and the mixture is cooled to room temperature to obtain a 40kg Cu-15Sn alloy ingot.
[0032] Example 3 Step 1: Weigh 40 kg of oxygen-free copper and high-purity tin (6 kg tin, 34 kg copper) with a purity of 99.99% using a high-precision electronic scale according to the Cu-15Sn alloy composition. Place the prepared metal raw materials into an ultrasonic cleaner for ultrasonic cleaning, and then dry them for later use. Machine blind holes on the end face of the copper block, and load high-purity tin granules into it according to the element ratio. Cover the top of the blind holes with a copper plate for sealing. Adjust the upper melting crucible to the loading position, and install the baseless crucible (120 mm inner diameter, 300 mm height) below. The bottom of the baseless crucible and the water-cooled copper crystallizer are assembled using a gradient contact sealed crystallization structure, with the two fitting tightly together to form a continuous guiding channel between the outlet of the baseless crucible and the inlet of the water-cooled copper crystallizer. The water-cooled copper crystallizer is equipped with a circulating cooling water channel, and the pull rod is also equipped with a cooling water channel. Both are circulated with high-speed cooling water, forming a continuous device structure of upper melting and lower directional solidification.
[0033] Step 2: The copper-based tin-embedded particle preform from Step 1, after ultrasonic cleaning and drying, is transferred into the melting crucible of the vacuum induction furnace. The melting crucible is made of high-purity graphite. Then, the casting channel is sealed: graphite paper with a carbon content >99.5% is laid along the inner wall of the funnel, ensuring complete adhesion between the graphite paper and the funnel wall to improve the sealing performance of the casting system; a guide pipe is installed to ensure the melting crucible, guide pipe, and baseless crucible are coaxial, and the inner wall of the baseless crucible is checked for smoothness and scratches. Then, the water-cooled copper crystallizer and the internal circulating cooling system of the pull rod are started, allowing high-speed cooling water to circulate continuously.
[0034] Step 3: Sequentially turn on the mechanical pump, Roots pump, fore-stage valve, and diffusion pump to evacuate the directional solidification furnace to the set vacuum level. Start the heating program to heat the holding zone, establishing a stable axial temperature gradient in the baseless crucible. Once the holding zone temperature reaches 1000℃, start the induction power supply to heat the melting crucible and begin melting the Cu-15Sn alloy. Start melting at 6kW, increasing by 3kW every 30 minutes. When the Cu-15Sn alloy in the melting crucible is completely melted and a stable vortex forms on the surface of the molten metal, adjust to 8kW for refining for 8 minutes. During the refining process, maintain continuous high-speed circulating cooling water inside the water-cooled copper crystallizer and pull rod to ensure the crystallizer maintains stable cooling capacity and forms a stable liquid-solid interface at the junction of the bottom of the baseless crucible and the water-cooled copper crystallizer.
[0035] Step 4: Molten Cu-15Sn alloy is poured into a baseless crucible using a tilting pouring method. The molten metal flows continuously into the baseless crucible in the lower heat preservation zone through a guide pipe and is held for 30 minutes. Then, a low-frequency AC current output device is activated, applying an AC current of 20Hz. This ensures the AC electromagnetic field primarily acts on the region near the liquid-solid interface of the baseless crucible, promoting melt flow and uniform solute distribution. Next, a pulling program is set, with the pulling rate set to 200μm / s, and the pulling device is activated. During the pulling process, the baseless graphite crucible remains stationary, with only the pulling rod slowly and continuously moving the solidified Cu-15Sn alloy ingot downwards. The bottom of the solidified alloy ingot remains in direct contact with the water-cooled copper crystallizer, rapidly forming a stable solidified shell under the action of high-speed circulating cooling water, continuously dissipating latent heat of solidification, thus maintaining a stable liquid-solid interface at the junction of the baseless crucible bottom and the water-cooled copper crystallizer. As the pulling process continues, molten metal is continuously replenished to the liquid-solid interface to complete continuous solidification. After pulling for 3000 seconds, the pulling and electromagnetic field output are stopped, and the mixture is cooled to room temperature to obtain a 40kg Cu-15Sn alloy ingot.
[0036] Example 4 Step 1: Weigh 40 kg of oxygen-free copper and high-purity tin (6 kg tin, 34 kg copper) with a purity of 99.99% using a high-precision electronic scale according to the Cu-15Sn alloy composition. Place the prepared metal raw materials into an ultrasonic cleaner for ultrasonic cleaning, and then dry them for later use. Machine blind holes on the end face of the copper block, and load high-purity tin granules into it according to the element ratio. Cover the top of the blind holes with a copper plate for sealing. Adjust the upper melting crucible to the loading position, and install the baseless crucible (120 mm inner diameter, 300 mm height) below. The bottom of the baseless crucible and the water-cooled copper crystallizer are assembled using a gradient contact sealed crystallization structure, with the two fitting tightly together to form a continuous guiding channel between the outlet of the baseless crucible and the inlet of the water-cooled copper crystallizer. The water-cooled copper crystallizer is equipped with a circulating cooling water channel, and the pull rod is also equipped with a cooling water channel. Both are circulated with high-speed cooling water, forming a continuous device structure of upper melting and lower directional solidification.
[0037] Step 2: The copper-based tin-embedded particle preform from Step 1, after ultrasonic cleaning and drying, is transferred into the melting crucible of the vacuum induction furnace. The melting crucible is made of high-purity graphite. Then, the casting channel is sealed: graphite paper with a carbon content >99.5% is laid along the inner wall of the funnel, ensuring complete adhesion between the graphite paper and the funnel wall to improve the sealing performance of the casting system; a guide pipe is installed to ensure the melting crucible, guide pipe, and baseless crucible are coaxial, and the inner wall of the baseless crucible is checked for smoothness and scratches. Then, the water-cooled copper crystallizer and the internal circulating cooling system of the pull rod are started, allowing high-speed cooling water to circulate continuously.
[0038] Step 3: Sequentially turn on the mechanical pump, Roots pump, fore-stage valve, and diffusion pump to evacuate the directional solidification furnace to the set vacuum level. Start the heating program to heat the holding zone, establishing a stable axial temperature gradient in the baseless crucible. Once the holding zone temperature reaches 1100℃, start the induction power supply to heat the melting crucible and begin melting the Cu-15Sn alloy. Start melting at 6kW, increasing by 4kW every 40 minutes. When the Cu-15Sn alloy in the melting crucible is completely melted and a stable vortex forms on the surface of the molten metal, adjust to 8kW for refining for 10 minutes. During the refining process, maintain continuous high-speed circulating cooling water inside the water-cooled copper crystallizer and pull rod to ensure the crystallizer maintains stable cooling capacity and forms a stable liquid-solid interface at the junction of the bottom of the baseless crucible and the water-cooled copper crystallizer.
[0039] Step 4: Molten Cu-15Sn alloy metal is poured into a baseless crucible using a flip-casting method. The molten metal flows continuously into the baseless crucible in the lower heat-preserving zone through a guide pipe and is held for 40 minutes. Then, a low-frequency AC current output device is activated, applying an AC current of 20Hz. This ensures the AC electromagnetic field primarily acts on the region near the liquid-solid interface of the baseless crucible, promoting melt flow and uniform solute distribution. Next, a pulling program is set, with the pulling rate set to 250μm / s, and the pulling device is activated. During the pulling process, the baseless graphite crucible remains stationary, with only the pulling rod slowly and continuously moving the solidified Cu-15Sn alloy ingot downwards. The bottom of the solidified alloy ingot remains in direct contact with the water-cooled copper crystallizer, rapidly forming a stable solidified shell under the action of high-speed circulating cooling water, continuously dissipating latent heat of solidification, thus maintaining a stable liquid-solid interface at the junction of the baseless crucible bottom and the water-cooled copper crystallizer. As the pulling process continues, molten metal is continuously replenished to the liquid-solid interface to complete continuous solidification. After pulling for 3000 seconds, the pulling and electromagnetic field output are stopped, and the mixture is cooled to room temperature to obtain a 40kg Cu-15Sn alloy ingot.
[0040] Example 5 Step 1 is the same as in Example 1; Step 2 is the same as in Example 1; Step 3: Sequentially turn on the mechanical pump, Roots pump, fore-stage valve, and diffusion pump to evacuate the directional solidification furnace to the set vacuum level. Start the heating program to heat the holding zone, establishing a stable axial temperature gradient in the baseless crucible. Once the holding zone temperature reaches 950°C, start the induction power supply to heat the melting crucible and begin melting the Cu-15Sn alloy. Start melting at 6kW, increasing by 3kW every 20 minutes. When the Cu-15Sn alloy in the melting crucible is completely melted and a stable vortex forms on the surface of the molten metal, adjust to 8kW for refining for 7 minutes. During the refining process, maintain continuous high-speed circulating cooling water in the water-cooled copper crystallizer and inside the pull rod to ensure the crystallizer maintains stable cooling capacity and forms a stable liquid-solid interface at the junction of the bottom of the baseless crucible and the water-cooled copper crystallizer.
[0041] Step 4 is the same as in Example 1.
[0042] Example 6 Step 1 is the same as in Example 1; Step 2 is the same as in Example 1; Step 3: Sequentially turn on the mechanical pump, Roots pump, fore-stage valve, and diffusion pump to evacuate the directional solidification furnace to the set vacuum level. Start the heating program to heat the holding zone, establishing a stable axial temperature gradient in the baseless crucible. Once the holding zone temperature reaches 1000℃, start the induction power supply to heat the melting crucible and begin melting the Cu-15Sn alloy. Start melting at 6kW, increasing by 2kW every 10 minutes. When the Cu-15Sn alloy in the melting crucible is completely melted and a stable vortex forms on the surface of the molten metal, adjust to 8kW for refining for 10 minutes. During the refining process, maintain continuous high-speed circulating cooling water in the water-cooled copper crystallizer and inside the pull rod to ensure the crystallizer maintains stable cooling capacity and forms a stable liquid-solid interface at the junction of the bottom of the baseless crucible and the water-cooled copper crystallizer.
[0043] Step 4: Molten Cu-15Sn alloy is poured into a baseless crucible using a flip-casting method. The molten metal flows continuously into the baseless crucible in the lower heat-preserving zone through a guide pipe and is held for 20 minutes. Then, a low-frequency AC current output device is activated, applying a 20Hz AC current to ensure the AC electromagnetic field primarily acts on the area near the liquid-solid interface of the baseless crucible, promoting melt flow and uniform solute distribution. Next, a pulling program is set, with the pulling rate set to 150μm / s, and the pulling device is activated. During the pulling process, the baseless graphite crucible remains stationary, with only the pulling rod slowly and continuously moving the solidified Cu-15Sn alloy ingot downwards. The bottom of the solidified alloy ingot remains in direct contact with the water-cooled copper crystallizer, rapidly forming a stable solidified shell under the action of high-speed circulating cooling water, continuously dissipating latent heat of solidification, thus maintaining a stable liquid-solid interface at the junction of the baseless crucible bottom and the water-cooled copper crystallizer. As the pulling process continues, molten metal is continuously replenished to the liquid-solid interface to complete continuous solidification. After pulling for 3000 seconds, the pulling and electromagnetic field output are stopped, and the mixture is cooled to room temperature to obtain a 40kg Cu-15Sn alloy ingot.
[0044] Comparative Example 1 This comparative example is basically the same as Example 3, except that in step 1, a copper block blind hole structure was not set; instead, Sn particles and Cu blocks were directly placed into the melting crucible. A gradient contact sealed crystallization structure was also not set, and cooling water was not circulated inside the pull rod. Additionally, a low-frequency alternating current was not applied in step 4. The specific steps are as follows: Step 1: Using a high-precision electronic scale, weigh 40 kg of oxygen-free copper (99.99% purity) and high-purity tin (6 kg tin, 34 kg copper) according to the Cu-15Sn alloy composition. Place the prepared metal raw materials into an ultrasonic cleaner for ultrasonic cleaning, and then dry them for later use. Adjust the upper melting crucible to the loading position, and install the base crucible (120 mm inner diameter, 300 mm height) below, with the bottom of the base crucible in contact with the water-cooled copper crystallizer. The water-cooled copper crystallizer is equipped with a circulating cooling water channel, through which high-speed circulating cooling water is introduced, forming a continuous device structure of upper melting and lower directional solidification.
[0045] Step 2: Place the copper blocks and tin granules weighed in Step 1 into the melting crucible of the vacuum induction furnace. The melting crucible is made of high-purity graphite. Then, seal the pouring channel: lay graphite paper with a carbon content >99.5% along the inner wall of the funnel, ensuring complete adhesion between the graphite paper and the inner wall to improve the sealing performance of the pouring system; install the guide pipe to keep the melting crucible, guide pipe, and base crucible coaxial, and check that the inner wall of the base crucible is smooth and free of scratches. Then, start the internal circulating cooling system of the water-cooled copper crystallizer to continuously circulate the high-speed cooling water.
[0046] Step 3: Sequentially turn on the mechanical pump, Roots pump, fore-stage valve, and diffusion pump to evacuate the directional solidification furnace to the set vacuum level. Start the heating program to heat the holding zone, establishing a stable axial temperature gradient in the crucible with the base. Once the holding zone temperature reaches 1000℃, start the induction power supply to heat the melting crucible and begin melting the Cu-15Sn alloy. Start melting at 6kW, increasing by 3kW every 30 minutes. When the Cu-15Sn alloy in the melting crucible is completely melted and a stable vortex forms on the surface of the molten metal, adjust to 8kW for refining for 8 minutes. During the refining process, maintain a continuous high-speed circulating cooling water supply inside the water-cooled copper crystallizer to ensure the crystallizer maintains a stable cooling capacity.
[0047] Step 4: Molten Cu-15Sn alloy is poured into a base-supported crucible using a tilting pouring method. The molten metal flows continuously into the base-supported crucible in the lower heat preservation zone through a guide pipe and is held in the heat preservation zone for 30 minutes. Then, a pulling program is set, with the pulling rate set to 200 μm / s and the pulling device started. After pulling for 3000 seconds, the pulling is stopped, and the mixture is cooled to room temperature to obtain a 40 kg Cu-15Sn alloy ingot.
[0048] The following performance tests were performed on the Cu-15Sn alloys prepared in Examples 1-4 and Comparative Example 1: like Figure 1 The figure shows a comparison of the microstructures of Cu-15Sn alloys prepared in Example 3 and Comparative Example 1. The alloy in Example 3 is a high-solute Cu-15Sn alloy obtained after electromagnetically confined directional solidification, while the alloy in Comparative Example 1 is a Cu-15Sn alloy obtained by electromagnetically confined directional solidification. As can be seen from the figure, electromagnetic confinement can effectively refine columnar and dendritic structures, break up coarse dendrites through Lorentz force, transform some columnar crystals into uniform and fine equiaxed grains, and significantly suppress Sn element segregation. This solves the problems of coarse dendrites, large grain size, poor microstructure, and severe solute segregation in Cu-15Sn alloys prepared by electromagnetically confined directional solidification.
[0049] Figure 2 The curves show the mechanical properties of the Cu-15Sn alloys prepared in Example 3 and Comparative Example 1. As can be seen from the curves, the tensile strength and elongation after fracture of the alloy prepared by the electromagnetic confinement synergistic directional solidification process are significantly higher than those of the sample without an electromagnetic field. This proves that the grain refinement and homogenization effects of the alternating electromagnetic field can effectively improve the alloy's ductility, toughness, and comprehensive mechanical properties, solving the problems of high brittleness and low mechanical properties of alloys prepared by traditional processes.
[0050] Figure 3The figure shows the conductivity comparison curves of Cu-15Sn alloys prepared in Example 3 and Comparative Example 1. As can be seen from the figure, under electromagnetic confinement, a large number of Sn atoms are uniformly dissolved in the Cu matrix, the degree of lattice distortion is improved, the corresponding conductivity is lower, and the axial conductivity fluctuation of the ingot is small. The sample without electromagnetic field has severe Sn segregation and low solid solubility, the overall conductivity is higher and the distribution is uneven along the length of the ingot. This curve can intuitively reflect the difference in the uniformity of Sn solid solution under the two processes.
[0051] Figure 4 The XRD comparison spectra of Cu-15Sn alloy prepared in Example 3 and Comparative Example 1 and pure copper show that the diffraction peak shift of the sample without electromagnetic field in Comparative Example 1 is small, the Sn solid solution content is low, and peritectic brittle impurity peaks are easy to appear. The diffraction peaks of the (111) crystal plane of the sample in Example 3 of this invention are significantly shifted, and the degree of lattice distortion is higher, which proves that a large number of Sn atoms are dissolved into the copper matrix. Moreover, there are no obvious brittle second phase diffraction peaks in the spectrum, indicating that electromagnetic-thermal flow synergistic regulation effectively suppresses peritectic transformation and obtains a single α solid solution structure with high solid solubility.
[0052] In addition, the electrical conductivity of the Cu-15Sn alloy material prepared in Example 1 was stable between 6.5% and 7% IACS, the X-ray diffraction angle of the (111) crystal plane was shifted by 0.323° compared with pure copper, and the mechanical properties were improved compared with the alloy of Comparative Example 1, with a tensile strength of 400 MPa and an elongation of 51%.
[0053] The electrical conductivity of the Cu-15Sn alloy material prepared in Example 2 was stable between 6% and 7% IACS. The X-ray diffraction angle of the (111) crystal plane was shifted by 0.35° compared with pure copper. At the same time, the mechanical properties were improved compared with the alloy of Comparative Example 1, with a tensile strength of 401 MPa and an elongation of 52%.
[0054] like Figures 2-4 As shown, the electrical conductivity of the Cu-15Sn alloy material prepared in Example 3 is stable between 4% and 5% IACS. The X-ray diffraction angle of the (111) crystal plane is 0.898° different from that of pure copper. At the same time, the mechanical properties are improved compared with the alloy of Comparative Example 1, with a tensile strength of 423 MPa and an elongation of 59%.
[0055] The electrical conductivity of the Cu-15Sn alloy material prepared in Example 4 was stable between 5% and 6% IACS. The X-ray diffraction angle of the (111) crystal plane was shifted by 0.378° compared with pure copper. At the same time, the mechanical properties were improved compared with the alloy of Comparative Example 1, with a tensile strength of 410 MPa and an elongation of 45%.
[0056] In summary, this invention provides a method for preparing large-size, low-segregation Cu-15Sn alloys using electromagnetic confinement. The Cu-15Sn alloy is melted using induction melting, and a flipping casting method effectively removes gas inclusions from the molten metal. During the drawing process of the alloy melt, an electromagnetic field is applied, and a Lorentz force is generated by an electromagnetic coil to agitate the molten metal at the solidification interface, breaking up coarse dendritic grains and achieving a grain refinement effect, effectively weakening the growth trend of coarse and brittle second phases. Simultaneously, the alternating magnetic field convection promotes Sn element diffusion, avoiding the formation of Sn element enrichment regions and shortening the Sn atom diffusion distance, allowing Sn to dissolve more uniformly into the Cu matrix, thus achieving solidification process control through the flow field. Furthermore, the electromagnetic confinement and heat flow control accelerate melt heat dissipation, promote rapid melt cooling, suppress phase transformation at the solid-liquid interface, increase the proportion of α-solid solution, achieve high solid solubility, and optimize the problems of uneven element distribution and solute enrichment caused by directional solidification processes without electromagnetic field confinement.
Claims
1. A method for preparing large-size, low-segregation Cu-15Sn alloys by electromagnetic confinement, characterized in that, Specifically: Step 1: Weigh oxygen-free copper and high-purity tin according to the composition of Cu-15Sn alloy, then process the copper block with blind holes and encapsulate the tin granules; assemble the melting crucible, guide tube, baseless crucible and water-cooled copper crystallizer coaxially from top to bottom in the vacuum induction furnace, and set cooling water channels inside the crystallizer and the induction furnace pull rod. Step 2: Place the raw materials into the melting crucible and seal the pouring channel; turn on the crystallizer and pull rod to cool the circulation. Step 3: Melt the Cu-15Sn alloy; Step 4: Pour the molten alloy into a baseless crucible, keep it warm, and then begin the pulling process. Apply alternating current during the pulling process. After the pulling is completed, a Cu-15Sn alloy ingot is obtained.
2. The method for preparing large-size, low-segregation Cu-15Sn alloys by electromagnetic confinement according to claim 1, characterized in that, In step 1, the total mass of the alloy is ≤50kg, and the purity of both copper and tin is 99.99%. After the metal raw materials are weighed, they are ultrasonically cleaned and dried. The top of the copper block is cut to obtain a copper plate. Blind holes are machined on the cut surface, tin granules are inserted into the blind holes, and a copper plate is placed on top of the blind holes for encapsulation.
3. The method for preparing large-size, low-segregation Cu-15Sn alloys by electromagnetic confinement according to claim 1, characterized in that, In step 1, the smelting crucible is made of high-purity graphite.
4. The method for preparing large-size, low-segregation Cu-15Sn alloys by electromagnetic confinement according to claim 1, characterized in that, In step 1, the bottom of the baseless crucible is in contact with the water-cooled copper crystallizer, and the two are fitted with an interference fit.
5. The method for preparing large-size, low-segregation Cu-15Sn alloys by electromagnetic confinement according to claim 1, characterized in that, In step 2, the specific steps for sealing the pouring channel are as follows: take graphite paper with a carbon content >99.5% and lay it along the inner wall of the funnel to ensure that the graphite paper is completely attached to the inner wall of the funnel; after sealing the pouring channel, turn on the high-speed cooling circulating water inside the water-cooled copper crystallizer and the pull rod.
6. The method for preparing large-size, low-segregation Cu-15Sn alloys by electromagnetic confinement according to claim 1, characterized in that, Step 3 specifically involves: The mechanical pump, Roots pump, fore-stage valve, and diffusion pump are turned on in sequence to evacuate the directional solidification furnace to the set vacuum level. The heating program is started to heat the holding zone, so that the baseless crucible can establish a stable axial temperature gradient. After the temperature of the holding zone rises to 800℃~1100℃, the induction power supply is turned on to heat the melting crucible and start melting Cu-15Sn alloy. During the melting process, the water-cooled copper crystallizer and the high-speed circulating cooling water inside the pull rod are kept running continuously.
7. The method for preparing large-size, low-segregation Cu-15Sn alloys by electromagnetic confinement according to claim 6, characterized in that, In step 3, the specific smelting process is as follows: Start melting at 6kW, increasing by 1kW to 4kW every 10 to 40 minutes. Once the Cu-15Sn alloy in the melting crucible is completely melted and a stable vortex forms on the surface of the molten metal, adjust to 8kW for refining for 2 to 10 minutes.
8. The method for preparing large-size, low-segregation Cu-15Sn alloys by electromagnetic confinement according to claim 1, characterized in that, Step 4 specifically involves: Molten Cu-15Sn alloy liquid was poured into a baseless crucible using a flip-casting method and held in the holding zone for 10 to 40 minutes. A 20Hz alternating electromagnetic field was applied by a low-frequency AC device, with the electromagnetic field concentrated on the liquid-solid interface region of the baseless crucible. A pulling device was started at a pulling rate of 100 to 250 μm / s, keeping the baseless crucible fixed. The pulling rod moved the solidified ingot downwards, and the bottom of the ingot continuously contacted the water-cooled copper crystallizer to dissipate latent heat and maintain the stability of the liquid-solid interface. After continuous pulling for 3000 seconds, the pulling device and electromagnetic field were turned off, and the furnace was cooled to room temperature to obtain the Cu-15Sn alloy ingot.